Discontinuous transcription generates heterogeneity at the leader fusion sites of coronavirus mRNAs. - Makino, S (1988)
Coronavirus mRNA is synthesized by a discontinuous transcription process, which involves a free leader RNA species. As a result, each virus-specific mRNA contains an identical leader RNA derived from the 5', end of the genomic RNA. In this study, we demonstrate by primer extension studies that the leader-fusion sites on a given species of coronavirus subgenomic mRNA are heterogeneous. The heterogeneity was due to variation in the number of pentanucleotide (UCUAA) repeats present at the leader fusion site. This pentanucleotide repeat region was complementary between the free leader RNA and the transcription start sites on the template RNA. This result suggests that the discontinuous transcription of coronavirus mRNAs occurs within the complementary sequences localized in two different RNA segments and that RNA joining occurs at variable sites.